Basin architecture controls on the chemical evolution and He-4 distribution of groundwater in the Paradox Basin - Tyne, RL; Barry, H; Cheng, A; Hillegonds, DJ; Kim, J-H; McIntosh, JC; Ballentine, CJ (Elsevier, 2022)
Fluids such as 4He, H2, CO2 and hydrocarbons accumulate within Earth's crust. Crustal reservoirs also have potential to store anthropogenic waste (e.g., CO2, spent nuclear fuel). Understanding fluid migration and how this is impacted by basin stratigraphy and evolution is key to exploiting fluid accumulations and identifying viable storage sites. Noble gases are powerful tracers of fluid migration and chemical evolution, as they are inert and only fractionate by physical processes. The distribution of 4He, in particular, is an important tool for understanding diffusion within basins and for groundwater dating. Here, we report noble gas isotope and abundance data from 36 wells across the Paradox Basin, Colorado Plateau, USA, which has abundant hydrocarbon, 4He and CO2 accumulations. Both groundwater and hydrocarbon samples were collected from 7 stratigraphic units, including within, above and below the Paradox Formation (P.Fm) evaporites. Air-corrected helium isotope ratios (0.0046 - 0.127 RA) are consistent with radiogenic overprinting of predominantly groundwater-derived noble gases. The highest radiogenic noble gas concentrations are found in formations below the P.Fm. Atmosphere-derived noble gas signatures are consistent with meteoric recharge and multi-phase interactions both above and below the P.Fm, with greater groundwater-gas interactions in the shallower formations. Vertical diffusion models, used to reconstruct observed groundwater helium concentrations, show the P.Fm evaporite layer to be effectively impermeable to helium diffusion and a regional barrier for mobile elements but, similar to other basins, a basement 4He flux is required to accumulate the 4He concentrations observed beneath the P.Fm. The verification that evaporites are regionally impermeable to diffusion, of even the most diffusive elements, is important for sub-salt helium and hydrogen exploration and storage, and a critical parameter in determining 4He-derived mean groundwater ages. This is critical to understanding the role of basin stratigraphy and deformation on fluid flow and gas accumulation.